Analysis of Student Ability Solving Hots Problems Material Exponent Equation Reviewed From's Beginning Ability - Nadifah, Lailatul; Shodikin, Ali (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2024)
This study aims to describe the ability of high school students in solving HOTS-type questions in terms of initial abilities. The research method used in this research is descriptive qualitative. The subjects of this study were three students of class X consisting of 1 high-ability student, 1 medium-ability student, and 1 low-ability student. Collecting data or information in this study using written tests and interviews. The written test was conducted twice, namely the initial ability test and the problem-solving test. The instrument used was a validated test and interview guide. The result of this study is that students who have high abilities turn out to have similarities with students who have moderate abilities, which are only able to solve problem number 1 with an analytical level (C4) even though they use different methods of solving. While students who have low abilities are not able to respond to the three questions correctly. In general, the ability of SMA Negeri 1 Baureno students in solving HOTS category questions is still below average. This is because they are not used to working on HOTS category questions at school. So far, teachers only give ordinary questions found in textbooks or worksheets.